Precision medicine in cow's milk allergy. Issue 3 (June 2020) - D'Auria, Enza; Venter, Carina
Abstract : Purpose of review: The aim of this review is to describe the role of precision medicine in the diagnosis, treatment, and monitoring of cow's milk allergy. Recent findings: The development of 'omics' sciences in the field of food allergy has led to a better understanding of the allergenicity of cow's milk proteins and significant advances in the knowledge of the pathogenesis and mechanisms of cow's milk allergy. Omics-based technologies allow the practitioner to better differentiate cow's milk allergy subtypes and to predict cow's milk allergy (CMA) persistence over time. Precision medicine extends the role of the oral food challenge, to determine the individual's threshold doses, and to establish tolerance to baked milk products. Other than symptom relief, dietary strategies are currently being investigated for the potential to induce tolerance. Oral immunotherapy offers a treatment option for patients with severe and persistent IgE-mediated CMA. Individual baseline-immune profiles may be predictive of cow's milk oral immunotherapy safety and efficacy. Patient data derived from current technology, in combination with the patient's history, can be translated into treatments targeted at patient-tailored interventions. Summary: The identification of novel biomarkers may improve diagnostic accuracy and also predict patient responsiveness to treatments. Integration of patient data will become increasingly important as omics technologies become more widely used in the clinical setting.